Regulatory Challenges of Anglo-Saxon Corporate Dispute Resolution Policy in Kazakhstan - Shiryn Baikenzhina; Gulzhazira Ilyassova; Karina Sabyrova; Yerdos Khamzin; Dana Abdakimova (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2025)
In recent years, Kazakhstan has incorporated selected elements of the Anglo-Saxon legal system as part of efforts to modernize its legal framework and create a favorable business environment. One of the most prominent manifestations of this approach is the establishment of the Astana International Financial Center (AIFC), which applies legal standards derived from common law traditions. This study aims to analyze the challenges associated with adapting common law mechanisms for the resolution of corporate disputes within Kazakhstan’s predominantly civil law, based legal system. The research employs a normative legal method with statutory and comparative law approaches to examine the fundamental principles governing corporate legal relations. The discussion focuses on three main aspects: (i) the implementation of common law practices and mechanisms in Kazakhstan as part of the process of global legal convergence; (ii) the application of common law standards and procedures in jurisdictions with civil law and mixed legal systems through comparative analysis, particularly in France and the United Arab Emirates; and (iii) the compatibility of common law elements with Kazakhstan’s legal framework, including the normative and institutional challenges affecting corporate dispute resolution. The findings indicate that although elements of case law have been increasingly integrated into corporate dispute resolution in non-common law jurisdictions, their application in Kazakhstan remains limited and is largely confined to the jurisdiction of the AIFC Court. Nevertheless, the emerging practice of this court demonstrates a gradual process of integration that holds promising prospects for the development of corporate dispute resolution in Kazakhstan.